APPLICATION OF HYPNOTEACHING METHOD TO IMPROVE SELF-CONFIDENCE AND RESULTS OF STUDENT MATHEMATIC LEARNING - Sari, Febriani Dwi; Prihatnani, Erlina (LPPM Undiksha, 2018)
This research aims to improve student’s mathematics learning outcomes and their self-confidence using the Hypnoteaching method on the learning of Algebra for class VIII A of Islam Sultan Fattah Salatiga Junior High School. This research is included as classroom action research. The model used in this research is the Kemmis & Mc Taggart’s which consists of 4 stages namely planning, implementation, observation, and reflection. The improvement of student’s learning outcomes and self-confidence in learning mathematics are seen from their grades and self-confidence questionnaire scores. On one hand, 1st cycle of questionnaire results show that student’s had experienced improvement in self-confidence by 58% with the average of student’s learning outcomes by 58.4% and 42% completeness. On the other hand, the 2nd cycle of questionnaire results show that students had experienced improvement in self-confidence by 79% with the average of student’s learning outcomes by 76.9% and 79% completeness